Analysis of risk factors for different subtypes of acute coronary syndrome. Issue 5 (May 2021) - Zhang, Lei; Hailati, Juledezi; Ma, Xiaoyun; Liu, Jiangping; Liu, Zhiqiang; Yang, Yuchun; He, Pengyi; Wulasihan, Muhuyati
Aims: To investigate the different risk factors among different subtypes of patients with acute coronary syndrome (ACS). Methods: A total of 296 patients who had ACS were retrospectively enrolled. Blood and echocardiographic indices were assessed within 24 hours after admission. Differences in risk factors and Gensini scores of coronary lesions among three groups were analyzed. Results: Univariate analysis of risk factors for ACS subtypes showed that age, and levels of fasting plasma glucose, amino-terminal pro-brain natriuretic peptide, and creatine kinase isoenzyme were significantly higher in patients with non-ST-segment elevation myocardial infarction (NSTEMI) than in those with unstable angina pectoris (UAP). Logistic multivariate regression analysis showed that amino-terminal pro-brain natriuretic peptide and the left ventricular ejection fraction (LVEF) were related to ACS subtypes. The left ventricular end-diastolic diameter was an independent risk factor for UAP and ST-segment elevation myocardial infarction (STEMI) subtypes. The severity of coronary stenosis was significantly higher in NSTEMI and STEMI than in UAP. Gensini scores in the STEMI group were positively correlated with D-dimer levels (r = 0.429) and negatively correlated with the LVEF (r = −0.602). Conclusion: Different subtypes of ACS have different risk factors. Our findings may have important guiding significance for ACS subtype risk assessment and clinical treatment.